Evaluation of Tourism Development Using the TALC Approach: A Case Study in East Lombok, Indonesia - Ahmad Kholis; M. Setyo Nugroho; Ma'ruf (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
This study aims to evaluate how the condition of the development of the tourist attraction of Labuhan Haji Beach, East Lombok in 2000-2022. The type of research used is historical research with a qualitative approach. The data collection method used is the observation method in the form of non-participatory observations in Labuhan Haji Beach, East Lombok, interviews with 6 informants (purposive sampling), and documentation studies. The analysis technique used is data reduction, data presentation, and conclusion drawing. The results of this study indicate that the current condition of the development of the Labuhan Haji Beach tourist attraction is in a cycle of stagnation towards rejuvenation. Tourist visits show fluctuating numbers from 2010-2021. The development of infrastructure facilities and infrastructure at Labuhan Haji Beach in 2000 did not go well because the Labuhan Haji Beach area was still a forest with dense tickets. The construction of facilities in the form of cleaning the coastal area as well as the construction of new road access was carried out in 2004. In addition, the development of amenities such as parking lots, berugak (gazebo), rest areas, lodging, and restaurants was carried out in order to meet the needs of tourists. There are also various policies implemented, namely the revitalization of the Labuhan Haji Pier, the arrangement and dredging of the Labuhan Haji Pier harbor pool, the construction of the Ancol Mini Tourist Park and the arrangement of the coastal area. This research contributes in providing recommendations to stakeholders, especially the public sector in formulating policies for the development of Labuhan Haji Beach, East Lombok. In addition, this research is expected to be a contribution in the form of academic literature regarding the evaluation of the development of a destination attraction in the area using the life cycle of a tourist destination.